2003
DOI: 10.1074/jbc.m208900200
|View full text |Cite
|
Sign up to set email alerts
|

A Scavenger Function for a DrosophilaPeptidoglycan Recognition Protein

Abstract: Recent studies of peptidoglycan recognition protein (PGRP) have shown that 2 of the 13 Drosophila PGRP genes encode proteins that function as receptors mediating immune responses to bacteria. We show here that another member, PGRP-SC1B, has a totally different function because it has enzymatic activity and thereby can degrade peptidoglycan. A mass spectrometric analysis of the cleavage products demonstrates that the enzyme hydrolyzes the lactylamide bond between the glycan strand and the cross-linking peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
293
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(300 citation statements)
references
References 26 publications
6
293
1
Order By: Relevance
“…Recently, it was reported that Drosophila PGRP-SC1B has a N-acetylmuramyl-L-alanine amidase activity and that it might have a scavenger function (47). Also, Drosophila PGRP-LB has been shown to have bacterial cell wall lytic activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that Drosophila PGRP-SC1B has a N-acetylmuramyl-L-alanine amidase activity and that it might have a scavenger function (47). Also, Drosophila PGRP-LB has been shown to have bacterial cell wall lytic activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…[19,29] with minor modification. Briefly, 40 mg lysozyme-treated Staphylococcus aureus PGN (Sigma, USA) at a concentration of 1 mg/mL was incubated with 50 mg protein extract of rOn-PGRP-SC2 in Tris-ZnCl 2 buffer (20 mM TrisHCl, 150 mM NaCl, 10 mM ZnCl 2 , pH 7.2) or Tris buffer (20 mM TrisHCl, 150 mM NaCl, pH 7.2).…”
Section: Assay For Amidase Activity Of Ron-pgrp-sc2mentioning
confidence: 99%
“…The activation of insect PGRPs by Gram-positive or Gram-negative bacteria may trigger Toll (Gobert et al, 2003) and immune deficiency (Imd) signal transduction pathways (Takehana et al, 2002) and the prophenol-oxidase cascade (Takehana et al, 2002), which results in the production of antimicrobial effectors. In addition, some insect PGRPs such as Drosophila PGRP-SC1 and PGRP-LB are N-acetylmuramoyl-L-alanine amidases (Kim et al, 2003;Mellroth et al, 2003), which can hydrolyze proinflammatory peptidoglycans. One insect PGRP, Drosophila PGRP-SA, which is not an amidase, has an L,D-carboxypeptidase activity for diaminopimelic acid-type tetrapeptide peptidoglycan fragments (Chang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%